Positive allosteric modulators of nonbenzodiazepine γ-aminobutyric acidA receptor subtypes for the treatment of chronic pain. Issue 1 (January 2019) - Johnstone, Timothy B.C.; Xie, Jennifer Y.; Qu, Chaoling; Wasiak, David J.; Hogenkamp, Derk J.; Porreca, Frank; Gee, Kelvin W.
Abstract : Abstract: Chronic neuropathic pain may be caused, in part, by loss of inhibition in spinal pain processing pathways due to attenuation of local GABAergic tone. Nociception and nocifensive behaviors are reduced after enhancement of tonically activated extrasynaptic GABAA R-mediated currents by agonist ligands for δ subunit–containing GABAA Rs. However, typical ligands that target δ subunit–containing GABAA Rs are limited due to sedative effects at higher doses. We used the spinal nerve ligation (SNL) and gp120 models of experimental neuropathic pain to evaluate compound 2-261, a nonbenzodiazepine site positive allosteric modulator of α4 β3 δ GABAA Rs optimized to be nonsedative by selective activation of β2/3 -subunit–containing GABAA Rs over receptor subtypes incorporating β1 subunits. Similar levels of 2-261 were detected in the brain and plasma after intraperitoneal administration. Although systemic 2-261 did not alter sensory thresholds in sham-operated animals, it significantly reversed SNL-induced thermal and tactile hypersensitivity in a GABAA R-dependent fashion. Intrathecal 2-261 produced conditioned place preference and elevated dopamine levels in the nucleus accumbens of nerve-injured, but not sham-operated, rats. In addition, systemic pretreatment with 2-261 blocked conditioned place preference from spinal clonidine in SNL rats. Moreover, 2-261 reversed thermal hyperalgesia and partially reversed tactile allodynia in the gp120 model of HIV-related neuropathic pain. The effects of 2-261 likely required interaction with the α4 β3 δ GABAA R because 2-301, a close structural analog of 2-261 with limited extrasynaptic receptor efficacy, was not active. Thus, 2-261 may produce pain relief with diminished side effects through selective modulation of β2/3 -subunit–containing extrasynaptic GABAA Rs. Abstract : Compound 2-261, a nonbenzodiazepine site positive allosteric modulator of α4 β3 δ GABAA Rs, was effective in reducing affective and sensory qualities of experimental neuropathic pain.